A Light Source - Sathian,J; Oxborrow,M (2017)
There is provided a light source arranged to output light at a first wavelength. The light source comprises a luminescent concentrator having a slab-shaped geometry. The luminescent concentrator comprises: an input port arranged to receive light and define a first area; an output port arranged to transmit light and define a second area which is smaller than the first area; and surfaces arranged to direct light inside the luminescent concentrator to the output port. The luminescent concentrator further comprises lumophores arranged to receive light at a second wavelength and emit light at the first wavelength; and a pump light supply coupled to the input port and arranged to illuminate the input port with light at the second wavelength.